2012
DOI: 10.1074/jbc.m111.279661
|View full text |Cite
|
Sign up to set email alerts
|

Dileucine and PDZ-binding Motifs Mediate Synaptic Adhesion-like Molecule 1 (SALM1) Trafficking in Hippocampal Neurons

Abstract: Background:The SALMs are neuronal cell adhesion molecules. Results: Deletion of the SALM1 PDZ-binding motif or mutation of a dileucine motif affects ER retention and surface expression. Conclusion: Enhanced SALM1 surface causes formation of elongated processes. Significance: SALMs can regulate neuronal morphology and may be involved in developmental disorders like autism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 73 publications
1
11
0
Order By: Relevance
“…This is somewhat surprising as usually di-leucine motifs are forward ER trafficking signals of G-protein coupled receptors [38][44]. However, the di-leucine motif of the synaptic adhesion-like molecule 1 (SALM1) also functions as ER retention signal [45]. It will be interesting to see if future studies reveal the mechanisms dictating such distinct ER trafficking responses to di-leucine motifs.…”
Section: Discussionmentioning
confidence: 99%
“…This is somewhat surprising as usually di-leucine motifs are forward ER trafficking signals of G-protein coupled receptors [38][44]. However, the di-leucine motif of the synaptic adhesion-like molecule 1 (SALM1) also functions as ER retention signal [45]. It will be interesting to see if future studies reveal the mechanisms dictating such distinct ER trafficking responses to di-leucine motifs.…”
Section: Discussionmentioning
confidence: 99%
“…[47][48][49][50] Among LRR proteins, LRFNs form a family of transmembrane cell adhesion molecules that promote changes in neuronal morphology, dendritic outgrowth and synapse formation. [51][52][53] It was further demonstrated that LRFNs form complexes with NMDARs, and promote the specialization of excitatory synapses. 24,52,53 In particular, the N-terminal domains of LFRN2 and NR1 interact directly, and this interaction regulates the surface expression of NMDARs in hippocampal neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The identities are predominantly restricted to the extracellular regions, whereas the sequences in the C-terminals are highly variable, demonstrating virtually no amino acid sequence identities except for the PDZ-domain-binding motifs, suggesting that the individual SALMs have distinct functions (Nam et al 2011 ;Seabold et al 2012 ;Mah et al 2010 ).…”
Section: Genes and Proteinsmentioning
confidence: 96%
“…However, only SALM4 and -5 form trans -homophilic interactions. These interactions are Ca 2+ independent and highly specifi c. Thus, SALM4 does not interact with SALM5 and vice versa (Seabold et al 2012 ).…”
Section: Interactionsmentioning
confidence: 99%